SUMBER INFORMASI PENGETAHUAN TENAGA KESEHATAN TENTANG PELAYANAN TUBERCULOSIS DI FASILITAS KESEHATAN PRIMER SWASTA KLINIK PRATAMA - Sinaga, Afifah Sahputri; Ritonga, Imelda Liana (Jurnal Ilmiah Keperawatan IMELDA, 2023)
Tuberculosis (TB) is one of the biggest global health problems after HIV (Human Immunodeficiency Virus). Tuberculosis is caused by Mycobacterium Tuberculosis and spreads through breathing. The aim of this research is to determine the source of information for health workers in private primary health facilities (Klinik Pratama) in the working area of ??the Terjun Community Health Center, Paya Pasir Village, Medan City. The research method used is a qualitative descriptive research type. The location of this research was carried out at the Pratama Clinic in the Working Area of ??the Terjun Community Health Center, Paya Pasir Village, Medan City. This research was carried out from March to August 2023. The number of participants in this research was 8 health workers who worked at the Pratama clinic. Research data was collected through in-depth interviews with participants and analyzed thematically. The research results consist of 3 themes, namely: 1 (sources of information for health workers in providing Tuberculosis services), 2 (Level of knowledge of health workers regarding tuberculosis services), 3 (Selection of health workers who receive Tuberculosis training). The conclusions from this research are: 1. Health workers at the Pratama Clinic get more information sources from the internet and posters. 2. The level of knowledge of health workers regarding the signs and symptoms of TB is sufficient, but the TB service facilities at the Pratama clinic are not yet satisfactory. 3. The health service visited the clinic but not all health workers took part in tuberculosis training, only those in the tuberculosis program took part (PIC TBC).